2021
DOI: 10.1136/bmjopen-2021-049565
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic risk factors for non-communicable diseases in Ethiopia: a systematic review and meta-analysis

Abstract: ObjectivesNon-communicable diseases (NCDs) are causing a new and yetsignificant health challenge in low-income countries. In Ethiopia, although 39% of deaths are NCD related, the health system remains underprepared, highlighting the clear need for evidence on risk factor distributions to inform resource planning and the health response. Therefore, this review investigates prevalence distributions and sex and age variations of metabolic risk factors among Ethiopian adults.Research design and methodsThis systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 112 publications
0
2
1
Order By: Relevance
“…The prevalence of hypertension has been increasing in developing countries, particularly in sub-Saharan Africa, partly attributed to unhealthy dietary habits: high dietary salt intake, and inadequate intakes of fruit and vegetable 3 . In Ethiopia, although some studies reported up to a 40% prevalence of hypertension, a recent systematic review of metabolic risk factors and the current study reveals that one in five (21%) adults are hypertensive 21 . Hypertension increases the incidence of chronic diseases unless prevention and control programs such as screening, identification, and treatment of cases and lifestyle interventions are strengthened 50 , 51 .…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…The prevalence of hypertension has been increasing in developing countries, particularly in sub-Saharan Africa, partly attributed to unhealthy dietary habits: high dietary salt intake, and inadequate intakes of fruit and vegetable 3 . In Ethiopia, although some studies reported up to a 40% prevalence of hypertension, a recent systematic review of metabolic risk factors and the current study reveals that one in five (21%) adults are hypertensive 21 . Hypertension increases the incidence of chronic diseases unless prevention and control programs such as screening, identification, and treatment of cases and lifestyle interventions are strengthened 50 , 51 .…”
Section: Discussioncontrasting
confidence: 53%
“…In developing countries like Ethiopia, suboptimal dietary consumptions, early-age chronic undernutrition caused by dietary insufficiency, and the growing burden of overweight/obesity in adults are overwhelming the national healthcare response 19 , 20 . Previous studies in Ethiopia identified several sociodemographic predictors of metabolic risk factors, including gender, marital status, residence, occupational status, income, and with individual risk factors such as inadequate fruit/vegetables intake, salt intake, physical inactivity, alcohol consumption, tobacco use, and khat chewing 21 25 . However, little is known about the association between dietary patterns and metabolic risk factors in the population.…”
Section: Introductionmentioning
confidence: 99%
“… 7 , 68 The chance of exposure to behavioral risk factors that are attributable to cause NCD, like alcohol consumption and physical inactivity, 69 and metabolic risks such as overweight/obesity and hypertension are also directly associated with the age of participants. 70 Our exploratory analysis presented in Supplementary Tables 1 and 2 shows that the age of adults is associated with employment status, family history of NCD, salt intake, alcohol consumption, khat use, and overweight and obesity; and with cardiovascular health concerns, cancer knowledge, physical activity, all which could augment the influence of age on the prevalence of NCD.…”
Section: Discussionmentioning
confidence: 95%